2010
DOI: 10.1007/s00395-010-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinases and phosphatases in ischaemic preconditioning: a re-evaluation

Abstract: Activation of several protein kinases occurs during myocardial ischaemia and during subsequent reperfusion. In contrast to the intensive investigation into the significance of kinase activation in cardioprotection, relatively little is known about the role of the phosphatases in this regard. The aim of this study was to re-evaluate the putative roles of PP1 and PP2A in ischaemia/reperfusion and in triggering ischaemic preconditioning. Isolated perfused working rat hearts were subjected to sustained global (15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…We therefore tested a much less selective PPase inhibitor, cantharidin. Five μM cantharidin during ischemia in rat hearts depressed post-ischemic function and did not limit infarct size [8]. While 1μM in our preliminary experiments was also ineffective (data not shown), a 10-fold lower dose (100 nM) had an anti-infarct effect (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We therefore tested a much less selective PPase inhibitor, cantharidin. Five μM cantharidin during ischemia in rat hearts depressed post-ischemic function and did not limit infarct size [8]. While 1μM in our preliminary experiments was also ineffective (data not shown), a 10-fold lower dose (100 nM) had an anti-infarct effect (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…We biopsied several cantharidin-treated hearts, but did not see any sign of preservation of ERK or MEK phosphorylation (data not shown). Since inhibition of PP2A, a prominent phosphatase in the heart, has previously been implicated in cardioprotection [8, 42], we investigated whether mild hypothermia could inhibit a protein phosphatase in vitro . The effect of mild hypothermia on an in vitro assay of PP2A is demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrated that Erk1/2 phosphorylation and c-Jun phosphorylation were associated with TNF-α expression in the infarcted heart. Since Erk1/2 and AP-1 have been shown to promote cell survival and IL-10 expression [6,12,38], further studies are required to determine their roles in regulating TNF-α expression and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of RISK signaling during reperfusion unites IPC, IPost and other agents that facilitate cardioprotection when offered either prior to ischemia or at reperfusion [10], and prolonging RISK activation by phosphatase inhibition during reperfusion also offers cytoprotection [8]. Of note, studies have questioned the importance of RISK in cardioprotection by IPost [27, 30] and in gentle reperfusion [23].…”
Section: Discussionmentioning
confidence: 99%